2015
DOI: 10.1039/c4ra14524k
|View full text |Cite
|
Sign up to set email alerts
|

Local structure of low-temperature γ-Al2O3 phases as determined by the luminescence of Cr3+ and Fe3+

Abstract: The g and g* phases of alumina synthesized from crystalline boehmite and pseudoboehmite were shown to strongly differ in some physicochemical characteristics. Photoluminescence of Cr 3+ and Fe 3+ as luminescent probes with their natural impurity concentrations was detected in the tested alumina samples and the local structure of the samples was examined. The crystal field strength and Racah parameters in g-Al 2 O 3 phases were determined. The ratio of octahedral and tetrahedral cationic positions was equal to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…5, curve b), which correspond to the 4 T 1 / 4 A 2 and 4 T 2 / 4 A 2 transitions. 8,23 The nanostructured Al 2 O 3 condensate not modied with chromium has PL in a range of 680-710 nm. Its PL intensity is much weaker as compared to that of Cr 3+ in a-Al 2 O 3 (Fig.…”
Section: Results Of Luminescence Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…5, curve b), which correspond to the 4 T 1 / 4 A 2 and 4 T 2 / 4 A 2 transitions. 8,23 The nanostructured Al 2 O 3 condensate not modied with chromium has PL in a range of 680-710 nm. Its PL intensity is much weaker as compared to that of Cr 3+ in a-Al 2 O 3 (Fig.…”
Section: Results Of Luminescence Studiesmentioning
confidence: 99%
“…Our earlier studies of the starting g-Al 2 O 3 showed that PL with l max ¼ 698 nm is caused mostly by octahedrally coordinated Cr 3+ ions (uncontrolled impurity) in the g-Al 2 O 3 matrix with the corresponding nonuniformly broadened 2 E / 4 A 2 transition. 8 The concentration of Cr 3+ ions in the samples of a-Al 2 O 3 target obtained from g-Al 2 O 3 was 10 À4 wt%, as estimated by the PL method. 8 Thus, it would be natural to expect PL of Cr 3+ ions to occur in the samples of Al 2 O 3 condensate produced by laser evaporation, even without the deliberate doping of the starting target.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is known that the binary system Al 2 O 3 ‐Cr 2 O 3 forms a complete solid solution by the octahedral substitution of Al 3+ for Cr 3+ . The resulting solid solution is commonly known as ruby . Ruby is known as a gemstone; however, it has remarkable applications in physics, optoelectronics, spintronics, fluorescent target for biomolecular imaging, and lasers .…”
Section: Introductionmentioning
confidence: 99%